2012
DOI: 10.1292/jvms.12-0281
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism of Craniodental Morphology in the Raccoon Dog <i>Nyctereutes procyonoides</i> from South Korea

Abstract: ABSTRAcT. We examined sexual dimorphism in the craniodental traits of the raccoon dog Nyctereutes procyonoides from South Korea. Univariate comparisons of skull (cranium and mandible) and dental measurements revealed a small extent of sexual dimorphism in some measurements. The most indicative dimorphic measurements were the breadths of the upper and lower canines which were around 8% larger in male specimens on average. On the other hand, multivariate analyses using only skull traits showed slightly a clearer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
(25 reference statements)
1
6
0
Order By: Relevance
“…This is similar to a previous study on the skull (cranium and mandible) of the raccoon dog (Kim et al, 2012), which reported that the breadth of the skull was around 8% larger in male specimens compared with females. Also, a study of the pelvis in raccoon dogs and red foxes found that pelvic bones of males were longer and broader than those of females (Jurgel_ enas, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is similar to a previous study on the skull (cranium and mandible) of the raccoon dog (Kim et al, 2012), which reported that the breadth of the skull was around 8% larger in male specimens compared with females. Also, a study of the pelvis in raccoon dogs and red foxes found that pelvic bones of males were longer and broader than those of females (Jurgel_ enas, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Gender identification of the human skeleton is important in bioarchaeological and forensic practice and is widely established, as demonstrated by numerous reports, for example on the trochlea, distal femur (Pinskerova et al, 2014), humerus (Kranioti and Michalodimitrakis, 2009), pelvis (Papaloucas et al, 2008) and cranium (KemkesGrottenthaler et al, 2002;Balci et al, 2005). Gender differences in bone morphology have also been reported to exist in many other animal species, such as the badger (Hidaka et al, 1998), dog (Kieser and Groeneveld, 1992a;Sajjarengpong et al, 2003), elephant (Todd, 2010), medaka fish (Shanthanagouda et al, 2014), moose (Duetsch and Peterson, 2012), raccoon dog (Hidaka et al, 1998;Kim et al, 2012;Jurgel_ enas, 2015) and red fox (Jurgel_ enas, 2015).…”
Section: Introductionmentioning
confidence: 90%
“…Regarding the lack of obvious size differences, one can wonder what is the effect of sexual dimorphism on the dentition of Nyctereutes. Kim et al (2012Kim et al ( : 1614 observed in N. procyonoides that "sexual difference is more apparent from data relating to the skull than that relating to the teeth". Taking into consideration these results, the size of the cheek teeth alone seems not useful for species differentiation given the lack of statistically significant samples for each species.…”
Section: Dentitionmentioning
confidence: 99%
“…2004) who recognized a distinct species N. vulpinus. These authors did not mention any differences to be interpreted as sexual dimorphism in the Saint-Vallier assemblage.On the other hand,Hidaka et al (1998) andKim et al (2012) observed some features indicating sexual dimorphism in the extant species N. procyonoides, such as stronger canine width, -Nyctereutes donnezani from Çalta, central Turkey, early Pliocene. Skull MNHN.F.ACA291, probably belonging to a male individual, in dorsal (A), occipital (B), ventral (C) and right lateral (D) views.…”
mentioning
confidence: 99%
“…The PI was calculated as each measurement divided by geometric mean of all measurements for each specimen to compare the relative length among populations (Darroch & Mosimann, 1985;Jungers, Falsetti & Wall, 1995;Koyabu & Endo, 2010). Data analyses were conducted without sexual distinction because previous reports document it as quite low or possibly absent in raccoon dog populations in several regions (Heptner et al, 1998;Hidaka et al, 1998;Kauhala et al, 1998b;Haba et al, 2008;Kim et al, 2012). We used oneway analysis of variance (ANOVA) with the Bonferroni correction for multiple comparisons to test craniometric variation among populations.…”
Section: Statistical Analysesmentioning
confidence: 99%